Harmonisation of prescribed punishment (Hadd) in Islamic Law and under the Malaysian penal law: a mere fantasy or a reality? - Mohamad Yunus, Mohamad Ismail (Institut Kefahaman Islam Malaysia (IKIM), 2005)
The implementation of hudud is generally seen as a necessary component of the Islamic resurgence movement and it is, as such, by no means confined to certain states. There are those, of course who maintain that the implementation of hudud offers a good answer to the problem of rising criminality and that in any case, Muslims have no choice in the matter of implementing divine law. On the other hand, a general expression of concern that implementing hudud under contemporary conditions where the individual is surrounded by an endless series of temptations might amount to oppression and injustice. This article aims at looking into the nature of hadd in the first place, reviewing the present Hudud Bills and trace the loopholes in them, and finally suggest some recommendations to solve the problem of implementing hudud law in a multiracial society like Malaysia.